2020
DOI: 10.1016/j.adolescence.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Family environment and school engagement:An investigation of cross‐lagged effects

Abstract: Introduction: Although an extensive body of work has shown that family functioning is linked to adolescent outcomes, less is known about how the family affects school outcomes and vice versa. The present longitudinal study tested reciprocal relationships between the family environment and school engagement during the middle school years. Methods: A cross-lagged latent model tested these effects in 378 Turkish youth (53.7% males; M = 11.73, SD = 0.53) evaluated annually (Waves 1, 2, and 3) in grades 6 through 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Considering that academic engagement is shaped by contextual factors, such as parental involvement ( Li et al, 2010 ), it is unclear how home confinement could influence young people's academic engagement. In a longitudinal study, adolescents who reported positive school engagement were more likely to perceive and report positive family environments over time ( Harris et al, 2020 ) in a way that families that maintained positive relations, even in the context of a pandemic and sanitary restrictions, could promote academic engagement in their children.…”
Section: Positive Family Environment Subjective Well-being and Academ...mentioning
confidence: 99%
“…Considering that academic engagement is shaped by contextual factors, such as parental involvement ( Li et al, 2010 ), it is unclear how home confinement could influence young people's academic engagement. In a longitudinal study, adolescents who reported positive school engagement were more likely to perceive and report positive family environments over time ( Harris et al, 2020 ) in a way that families that maintained positive relations, even in the context of a pandemic and sanitary restrictions, could promote academic engagement in their children.…”
Section: Positive Family Environment Subjective Well-being and Academ...mentioning
confidence: 99%
“…Thus, the quality of family relationships and communication constitutes an impact factor regarding the well‐being of young people (Guedes et al., 2022; Yubero et al., 2018). Family functioning has also emerged in the literature as a factor related to young people's school involvement and motivation (Harris et al., 2020; Stubbs & Maynard, 2017). A more positive family environment constitutes a facilitator element for the involvement of parents in their children's activities, promoting a more significant support structure for their learning and academic performance (Xia et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The bidirectional interactions between adolescents and the microsystem context directly influence adolescents’ development ( Kim, 2015 ). Prior studies have examined individual factors (age) and microsystem factors (home environment, family environment, parenting, neighborhood context, teacher quality, and school context) that predict students’ school engagement ( Chiu et al, 2012 ; Lam et al, 2012 ; Wang and Eccles, 2012a ; Shi et al, 2013 ; Wang and Chang, 2018 ; Harris et al, 2020 ). The macrosystem is the most distal and broadest context and influences adolescents’ development and other contexts (including microsystems).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the microsystem environment (family, class, and school) and the development of youth has been examined widely ( Dotterer and Lowe, 2011 ; Vanwynsberghe et al, 2017 ; Harris et al, 2020 ). However, few studies have focused on the association of macrosystems (such as the urban environment) with the academic development of adolescents.…”
Section: Introductionmentioning
confidence: 99%